Populisms not Populism: A Conversation with Judith Butler (Interview with Massimo Filippi and Enrico Monacelli) - Filippi, Massimo; Butler, Judith; Monacelli, Enrico (Scenari, 2021)
The most important political movements of the populist moment have been hardly legible for most of our modern political categories. From the Gilles Jaunes in France to the Hong Kong riots against Chinese imperialism, the current forms of revolt have been slippery and elusive to our comprehension. We, the respectable and detached viewers of these movements, simply couldn’t grasp these uprisings, as if they did not belong in the realms of political philosophy. Why is this the case? What is happening around the world? What sort of movements are shaking the planet? In order to answer these questions, the interviewers have turned to one of the most important philosophers of our time, a thinker whose thought has shaped, in some sense, the structure of the present form of revolt and contestation: Judith Butler. In the present contribution the interviewers have asked her opinion on some of the most pressing issues which face us all, while engaging with the current predicament: from the question of populism to the transfeminist mobilizations to the weird protests which are shaping our present and, finally, to the problem of sexual difference and political sovereignty.